The end of the 'new world order'?: Security governance and US imperialism after 9/11 - Elke Krahmann (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
The concept of global governance has emerged as a key theoretical approach since the 1990s. Applied to the transformation of international security, it has suggested a shift from the state-dominated bipolar system of the Cold War era to a new multipolar and multilateral security architecture in which state, non-state and international actors collaborate in the making and implementation of security policies. Then came September 11, 2001 and the war in Iraq. Today we appear to be more likely to discuss the nature of American hegemony and the stability of a unipolar international system. Observing the clash between these two competing perspectives of international security, the aims of this paper are threefold. First, this paper seeks to examine the respective theoretical assumptions underlying the concepts of hegemony and governance. Second, it examines the competing hypotheses proposed by these two theories with regard to international security. Third, it discusses in how far the empirical evidence since September 11, can be taken as indication of either a hegemonic strategy by the United States and balancing or bandwagoning behaviour by other major powers, or the continuation of security governance.
Keywords: 300; Imperialismus; Amerikanisch; USA; Welt